PROSPECTIVE TEACHERS’ FAMILIARITY AND EXPECTATION TOWARD THE IMPLEMENTATION OF STUDENT-CENTERED ENGLISH LANGUAGE TEACHING METHODS - Arina Shofiya; Nanik Sri Rahayu (UPT Bahasa Universitas Islam Negeri Sayyid Ali Rahmatullah Tulungagung, 2025)
The development of science and technology brings some impacts to various aspects of life, mainly English Language Teaching (ELT). . However, there is a shift of paradigm as the effect of modernization in ELT, the students become the main subjects of learning and the teaching methods are more student-centered. The prospective teachers need to understand any changes of teaching theories and make adjustment in their future practices. The present research is intended to answer the following research questions: 1) To what extent are the prospective teachers familiar with student-centered English language teaching methods?, 2) What is the perceived contribution of the student-centered English language teaching methods toward their knowledge development?, 3) What do the prospective teachers expect from the student-centered English language teaching methods? The research employed survey design involving 218 students of the fifth semester. The findings reveal that 1) the students show high familiarity to students-centered ELT methods, 2) the methods contribute to the development of their knowledge by providing theory and practices of student-centered ELT method, and 3) they have high expectation in mastering the theories and practice of student-centered ELT methods.